2019
DOI: 10.1111/1750-3841.14634
|View full text |Cite
|
Sign up to set email alerts
|

Berry Jelly: Optimization Through Desirability‐Based Mixture Design

Abstract: Berries are among the nutritionally richest fruits and the mixing of these fruits can originate products with peculiar characteristics and added value, since the fruit mixture allows adding nutritional and sensory value to the final product. Thus, in this study we aimed to optimize a mixed berry jelly formulation of red fruit (blackberry, blueberry, and strawberry), through the mixture design, desirability function, and response surface methodology. The fruit mixture influenced the physical–chemical, sensory, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 36 publications
3
12
0
Order By: Relevance
“…Regarding acidity, the pH of the jellies ranged from 2.91 to 3.98. These values are similar to those observed by Schiassi et al (2019), who reported a pH of 3.57 for blackberry jellies. According to Jackix (1988), the optimum pH for making jellies is around 3.50, a similar value found in the present study.…”
Section: Physical-chemical and Physical Properties Of Blackberry Jelliessupporting
confidence: 91%
See 1 more Smart Citation
“…Regarding acidity, the pH of the jellies ranged from 2.91 to 3.98. These values are similar to those observed by Schiassi et al (2019), who reported a pH of 3.57 for blackberry jellies. According to Jackix (1988), the optimum pH for making jellies is around 3.50, a similar value found in the present study.…”
Section: Physical-chemical and Physical Properties Of Blackberry Jelliessupporting
confidence: 91%
“…Through the average table (Table 4), it can be seen that the jelly made with coconut sugar was the least accepted for all the sensory attributes evaluated, presenting means of "indifferent" acceptance, while the others formulations (crystal, refined, demerara and brown) were the most accepted, with higher average acceptance scores, ranging between the terms "somewhat liked it " and "neither liked/nor disliked". Schiassi et al (2019) evaluating blackberry juice obtained similar results, with average sample scores between 6 and 8 on the hedonic scale ("I liked it a little" and "I liked it a lot"). Except for jelly prepared with coconut sugar, the jellies showed satisfactory results since according to Lawless & Heymann (2010), the assignment of scores with a score of 6 to 9 guarantees the product will be accepted by a marketing team from a sensorial.…”
Section: Sensory Analysismentioning
confidence: 62%
“…In the beverages segment, the fruit processing industries are developing differentiated products composed of two or more fruits, and this market is expanding increasingly (Souza et al, 2012;Pelegrine et al, 2015;Curi et al, 2019;Schiassi et al, 2019). The development of mixed juices is a viable alternative available to the industry, with the purpose of elaborating exclusive and healthier drinks because the combination of fruits can enhance nutritional characteristics (increase in the content of vitamins, minerals and soluble solids of the product) and sensorial quality (improving colour and consistency and balancing weak, mild and strong flavours, mainly with high acidity, astringency, or bitterness of certain fruits), thereby adding value to the final product (Sobhana et al, 2015;Curi et al, 2017;Schiassi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…We can observe that the appearance and its corresponding color attribute are important sensory factors. Color of foods greatly influences consumer preferences, and this trend can be observed in studies of Schiassi et al (2018) and Schiassi et al (2019). One of the main sensory parameters for the quality of foods is their color, and it is the first characteristic attracting consumer attention.…”
Section: Resultsmentioning
confidence: 97%
“…These fruits are capable of producing jams, jellies and juices with different tastes and appearances. Mixed fruit jams combine the sensory and nutritional aspects of two or more fruits in the final product, and this market is gradually gaining prime space in the consumer market (Schiassi et al, 2018, Farias et al, 2019Schiassi et al, 2019). A gamma regression model is considered in which the mean of the response variable depends on the values of the regressor variates according to an exponential link function, which is an alternative to consider for variables that seem to be highly skewed.…”
Section: Introductionmentioning
confidence: 99%